Formación de profesores prácticos reflexivos mediante la articulación de la investigación acción crítica y la práctica profesional reflexiva - Carbajal Lavado, Napoleón Santiago (2013)
In this research work it has been examined the conceptions of the students of the initial and primary education careers at the Institute of Higher Education "Indoamérica" of Trujillo, Peru, about the professional practice activities and the research in education and it has also been developed a plan of improvement for teachers to be reflective practitioners within the context of LISTON Y ZEICHNER (1997), SCHÖN (1992), CARR Y KEMIS (1988), CARR (1996), ELLIOT (1993) Y KEMIS (1988).theories. The examination of the student conceptions was made by making a diagnosis that consisted of a Likert scale type to a sample of 30 students and a focus group questionnaire to a sample of 8 students. It was developed and applied a plan of improvment for teacher training as reflective practitioners which was based on the portfolio and field diary of Zabalza (2003), the cycles of reflection on action Schon (1992), the workshops and systematization of DINFOCAD update - UFOD (2003) and improvement plans of Rodriguez (2005). The application of the improvement plan reported a 25% increase in teaching skills to: investigate, reflect, and produce practical knowledge, decision making and problem solving.